Properties of Artificial Lightweight Aggregates from Various Pozzolan Materials – A Review - D.L. Chuan Hao; R.A. Razak; Z. Yahya; M.M. Al Bakri Abdullah; A. Abdullah (Archives of Metallurgy and Materials)
The use of lightweight aggregate can bring advantages to the construction field. Lightweight aggregate has been used due to its lower density and can reduce the dead load applied to the structural elements. Due to the number of natural resources, such as natural aggregate having decreased, producing lightweight aggregate from industrial waste materials can overcome the problem. Different methods produce lightweight aggregates, such as sintering, cold bonding, and autoclaving. From earlier studies, spherical sintered lightweight aggregate can manufacture structural concrete. Using artificial lightweight aggregate in concrete can achieve the minimum strength requirement of structural concrete and has been applied in the construction field. The properties of lightweight aggregate, such as specific gravity, water absorption, crushing strength, and impact value, are reviewed. Besides that, the mechanical and thermal properties review is also important for using lightweight aggregate in concrete. The review also indicates that aggregate produced using the cold bonding method and autoclaving method potential can be used in the concrete.